Fructus Ligustri Lucidi aqueous extract promotes calcium balance and short-chain fatty acids production in ovariectomized rats. (28th October 2021) - Chen, Beibei; Wei, Junping; Zhu, Ruyuan; Zhang, Hao; Xia, Bingke; Liu, Yage; Dai, Xuan; Ye, Zimengwei; Tian, Yimiao; Li, Rui; Zhao, Dandan; Mo, Fangfang; et al.
Abstract: Ethnopharmacological relevance: Fructus Ligustri Lucidi (FLL) is an edible herb with anti-osteoporotic activity, yet whether and how the aqueous extract of this herb affect calcium metabolism in preservation of bone quality remain unclear. Aim of the study: To investigate the effects of FLL aqueous extract on calcium balance and short-chain fatty acids (SCFAs) production in ovariectomized (OVX) rats. Materials and methods: OVX rats were daily and orally administrated with FLL aqueous extract (3.5 g/kg) for 14 weeks. The levels of N-terminal propeptide of type I collagen (PINP) and C-terminal telopeptide of type I collagen (CTx-I) in rat serum were evaluated by ELISA assays. The concentration of calcium in serum, urine, and feces were determined by biochemical assays. Bone quality was determined by Micro-CT, a three-point bending assay, and Fourier Transform Infrared (FTIR) Spectrometry. The expressions of Calbindin D28K and Calcium-sensing receptor (CaSR) in kidney as well as the Vitamin D receptor (VDR), the transient receptor potential vanilloid receptor 6 (TRPV6), Calbindin D9k in the duodenum were measured by immunohistochemistry, western blotting, or real-time PCR. The short-chain fatty acids (SCFAs) levels in the feces of the cecum were tested by gas chromatograghy. Results: The administration of FLL to OVX rats resulted in a significant improvement in bone mineral density and biomechanical strength as well as in maintaining bone microstructures and material quality. Meanwhile, the decreased levels of PINP and increased levels of CTx-I in OVX rats were restored by FLL treatment. Additionally, FLL treatment increased calcium absorption, upregulated VDR, TRPV6, Calbindin D9k expressions in the duodenum, Calbindin D28K in kidney, and down-regulated CaSR expression in the kidney, as well as enhanced SCFAs levels in the feces of OVX rats. Conclusions: FLL aqueous extract may preserve bone quality through regulation of the calcium balance and intestinal SCFAs production in OVX rats. This offers translational value of FLL into osteoporosis clinical trial. Graphical abstract: Image 1